Early identification of axial psoriatic arthritis among patients with psoriasis: a prospective multicentre study. Issue 11 (3rd August 2022) - Proft, Fabian; Lüders, Susanne; Hunter, Theresa; Luna, Gustavo; Rios Rodriguez, Valeria; Protopopov, Mikhail; Meier, Katharina; Kokolakis, Georgios; Ghoreschi, Kamran; Poddubnyy, Denis
Abstract : Objectives: To evaluate a dermatologist-centred screening tool followed by a structured rheumatological examination including MRI of sacroiliac joints and spine for the recognition of psoriatic arthritis with axial involvement (axPsA). Methods: This was a prospective multicentre study. Adult patients with a confirmed diagnosis of psoriasis who had chronic back pain (≥3 months), onset <45 years and had not been treated with any biologic or targeted synthetic disease-modifying antirheumatic drug in the 12 weeks before screening were referred to a specialised rheumatology clinic. A rheumatological investigation including clinical, laboratory and genetic assessments as well as imaging with conventional radiography and MRI of sacroiliac joints and spine was performed. The primary outcome of the study was the proportion of patients diagnosed with axPsA among all referred patients with PsO. Results: Rheumatologists examined 100 patients of those who qualified for referral. 14 patients (including 3 with both axial and peripheral involvement) were diagnosed with axPsA and 5 were diagnosed with peripheral PsA solely. All patients diagnosed with axPsA had active inflammatory and/or structural (post)inflammatory changes in the sacroiliac joints and/or spine on imaging. In five patients, MRI changes indicative of axial involvement were found only in the spine. All but one patient with PsA (13/14 with axPsA and 5/5 with pPsA) fulfilled the Classification Criteria for Psoriatic Arthritis criteria for PsA. The Assessment of SpondyloArthritis International Society criteria for axSpA were fulfilled in 9 (64.3%) patients diagnosed with axPsA. Conclusions: Applying a dermatologist-centred screening tool may be useful for the early detection of axPsA in at-risk patients with psoriasis .